Multiband hairpin-line bandpass filters by using metamaterial complimentary split ring resonator - Mohd Fairus Mohd Yusoff; Muhammad Akram Mohd Sobri; Farid Zubir; Zaharah Johari (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
Telecommunication systems for the new generation have greatly stimulated the demand for multi-band bandpass ﬁlters with compact dimensions, low insertion loss, robust, low cost and less complex design. In this paper, a compact multi-band bandpass filter, with the fractional bandwidth of 40% and 20% at resonant frequency 3.5 and 5.5 GHz respectively with the response of Chebyshev passband ripple of 0.1 dB is presented. This bandpass filter is suitable for WiMAX application. The design is based on the hairpin-line configuration and metamaterial of complementary split ring resonator structure. The hairpin-line is used for the compact structure design and easy to fabricate because it has open-circuited ends that require no grounding. While the complementary split ring resonator structure is easy to design and can provide multi-band without affecting of size and performance of the filter. The simulated results show the dual-band bandpass response with the insertion loss is 0 dB and high attenuation at stopband. The proposed ﬁlter provides a compact, low insertion loss, and less complex structure design that are promising candidates in order to meet the demands of the new generation of communication systems.